2017
DOI: 10.1080/1828051x.2017.1344937
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic infections in dogs involved in animal-assisted interventions

Abstract: Animal Assisted Interventions (AAIs) programmes have been considered useful in different settings, such as hospital, therapeutic, educational and assisted living environments. In these contexts, all animals, and particularly dogs, should be subjected to appropriate health controls to prevent a potential risk of transmission of zoonotic agents. Domestic dogs are reservoirs of many zoonotic pathogens including several gastrointestinal parasites (protozoa and helminths). Therefore, the aim of the present study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…The co-therapist dogs underwent regular health and behavioral checks, carried out in collaboration between our Department and Public Veterinary Service of the “ASL Napoli1”. In addition, for each session, disinfectant wipes (chlorhexidine, ethylene diamine tetra acetic acid-tromethamine (Tris-EDTA), zinc gluconate, and glycerin) were used to clean the coat, the claws, and the tail of the dog to avoid the transmission of zoonotic agents (e.g., bacteria, fungi, parasitic elements) [ 21 , 22 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The co-therapist dogs underwent regular health and behavioral checks, carried out in collaboration between our Department and Public Veterinary Service of the “ASL Napoli1”. In addition, for each session, disinfectant wipes (chlorhexidine, ethylene diamine tetra acetic acid-tromethamine (Tris-EDTA), zinc gluconate, and glycerin) were used to clean the coat, the claws, and the tail of the dog to avoid the transmission of zoonotic agents (e.g., bacteria, fungi, parasitic elements) [ 21 , 22 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…At T1 and T2 of each AAA session, disinfectant wipes (chlorhexidine, TRIS-EDTA, zinc gluconate and glycerin) were used to clean the coat, the fingertips, and the tail of the dog to avoid the transmission of zoonotic agents (e.g., bacteria, fungi, parasitic elements) [60,61,62,63,64,65]. When the dog fidgeted (for example, screaming, slapping) and did not respond to attempts to redirect its behaviour, the veterinarian intervened promptly to minimize the effects of the stressful situation by changing the activity, maintaining a distance between the dog and the stressful stimulus or putting the dog in resting condition on the mat with an “oral discharge” [16].…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, Shen et al [ 9 ] showed that bodily contact significantly influenced the effectiveness of AAT. On the other hand, during these interventions, because of repeated contact with the dog’s mucosae (e.g., mouth mucosa), patients can be exposed to zoonotic pathogens (e.g., bacteria, viruses, and fungi) transmitted by the dog through direct contact [ 3 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Several reports describe human P. multocida infections acquired subsequent to close contact with a dog, such as sharing a bed or by licking or sniffing [ 10 , 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%